Applications of single‐cell sequencing for the field of otolaryngology: A contemporary review. Issue 3 (27th April 2020) - Pyle, Madeline P.; Hoa, Michael
Abstract: Objectives: Single‐cell RNA sequencing (scRNA‐Seq) is a new technique used to interrogate the transcriptome of individual cells within native tissues that have already resulted in key discoveries in auditory basic science research. Rapid advances in scRNA‐Seq make it likely that it will soon be translated into clinical medicine. The goal of this review is to inspire the use of scRNA‐Seq in otolaryngology by giving examples of how it can be applied to patient samples and how this information can be used clinically. Methods: Studies were selected based on the scientific quality and relevance to scRNA‐Seq. In addition to mouse auditory system (inner ear including hair cells and supporting cells, spiral ganglion neurons, and inner ear organoids), recent studies using human primary cell samples are discussed. We also perform our own analysis on publicly available, published scRNA‐Seq data from oral head and neck squamous cell carcinoma (HNSCC) samples to serve as an example of a clinically relevant application of scRNA‐Seq. Results: Studies focusing on patient tissues show that scRNA‐Seq reveals tissue heterogeneity and rare‐cell types responsible for disease pathogenesis. The heterogeneity detected by scRNA‐Seq can result in both the identification of known or novel disease biomarkers and drug targets. Our analysis of HNSCC data gives an example for how otolaryngologists can use scRNA‐Seq for clinical use. Conclusions: Although there are limitations to the translation of scRNA‐Seq to the clinic, we show that its use in otolaryngology can give physicians insight into the tissue heterogeneity within their patient's diseased tissue giving them information on disease pathogenesis, novel disease biomarkers or druggable targets, and aid in selecting patient‐specific drug cocktails. Abstract : Uses of single‐cell RNA sequencing (scRNA‐Seq) in clinical medicine. scRNA‐Seq characterizes tissue heterogeneity including diseased and rare cell types allowing for identification of unique genes expressed by these cells that might have been obscured by traditional RNA‐Seq and that may be used as potential drug targets. Interrogation of drug target expression within each cell cluster can aid in creating a patient‐specific drug cocktail. scRNA‐Seq can also be performed before or after treatment to get a sensitive picture of how a patient responded with elimination of diseased cells, continued presence of diseased cells unaffected by treatment, or emergence of new drug‐resistant clones.